Effects of Age on Microglial Responses to Cellular Stress Induced by Lipopolysacharides and Beta Amyliod - Subramaiam, Hemavathy (2011)
Microglia are the resident macrophages of the central nervous system (CNS). In the normal CNS, they are in a resting condition, characterised by low expression of MHC class II (MHC II) and co stimulatory molecules such as CD40. Following activation by various stressors, microglia acquire an inflammatory phenotype and the continuous activation of microglia is thought to exacerbate neuronal damage. It is also believed that with increasing age, the inflammatory response of microglia becomes uncontrolled. In this study, the effects of age on microglia responses were determined by culturing microglia from Sprague Dawley rats of 6 days (neonates), 2-4 months (adult) and 3 years (old). Microglia were then activated with lipopolysaccharide (LPS; 1μg/ml) or beta amyloid (Aβ; 25 or 50μg/ml) and assessed for expression of CD40 and MHC II activation markers, nitric oxide (NO) production and proliferative capacity at pre-determined time points. Adult microglia were difficult to culture, therefore ptimisations were carried out to support and enhance cell growth by coating culture flasks with poly-L-lysine and supplementing culture with insulin-transferrin-selenium (ITS) and macrophage colony stimulating factor (M-CSF). Expression of CD40 and MHC II was determined by immunophenotyping. Basal expression of CD40 and MHC II was higher in older microglia compared to neonates. Similarly, after activation with LPS and Aβ, CD40 and MHC II expression was higher in older cells. Upon LPS stimulation, the CD40 and MHC II expression was as follows:neonates, 11.3 ± 1.8% and 4.2 ± 2.3%; 2-4 months, 32.4 ± 25.2% and 21.2 ± 8.8%; 3 years, 26.4 ± 15.3% and 21.1 ± 12.6% respectively. Upon stimulation with Aβ, the CD40 and MHC II expression was: neonates, 50.3 ± 19.8% and 3.6 ± 1.4%; 2-4 months, 63.9 ± 24.5% and 36.9 ± 7.4%; 3 years, 75.2 ± 24.1% and 15.1 ± 11.5% respectively. The higher expression of CD40 and MHC II in older microglia is indicative of its potential for subsequent activation of T cells. Using the Griess assay and [3H]-thymidine roliferation assay, it was observed that the NO production and proliferation rate was induced at 48hrs and 18hrs time point respectively. Under resting condition, older microglia released marginally higher NO compared to neonates (p<.05); however, upon stimulation, older microglia released significantly lower (p<.05) NO production compared to neonates. Under resting condition, the NO production was as follows: neonates, 2.0μM; 2-4 months, 6.9μM and 3 years, 5.3μM. Upon stimulation with LPS and 50μg/ml Aβ, the NO production was: neonates, 29.3 and 60.2μM; 2-4 months, 11.9 and 9.9μM; 3 years, 9.9 and 5.7μM respectively. As for the proliferation capacity,older cells displayed significantly lower proliferation (p<.05) both when resting and upon stimulation, compared to neonates. In the resting condition, 2-4 months and 3 years old microglia recorded readings of 39929 cpm and 37328 cpm lower compared to neonates. Upon stimulation with LPS and 50μg/ml Aβ, proliferation rate of older microglia were consistently lower compared to neonates. Thus, as a result of our work, we demonstrated differences between primary neonatal and adult microglia responses to LPS and Aβ stimulation by comparing activation profiles, NO and proliferation rate. We demonstrated that although older cells exhibit a higher activation state upon stimulation (based on CD40 and MHC II expression), their functional aspects such as NO production and proliferation remain significantly low compared to neonate